SISTEM E-COMMERCE PADA PT UNIBINDO PERTIWI - Rudy, Rudy; Thee, Christina Amianco; Henrik, Henrik; Linda, Linda (Bina Nusantara University, 2007)
Article to designed e-Commerce system application based on analysis of the ordering and selling system.The used research methods were analysis and design system. This research tries to achieve an e-Commerce sitefacility that was able to be used by customer. Hopefully, the e-Commerce system functioned as service supportingsystem in a company, able to help the customer in making buying transaction more easily, there is online chatfacility , message and suggestion, also providing full information so it is easy to use and interesting.Keywords: e-Commerce, e-Commerce system